Metabolic Modeling Identifies Key Constraints on an Engineered Glycine Betaine Synthesis Pathway in Tobacco - McNeil, Scott D. (American Society of Plant Physiologists, 2000)
Previous work has shown that tobacco (Nicotiana tabacum) plants engineered to express spinach choline monooxygenase in the chloroplast accumulate very little glycine betaine (GlyBet) unless supplied with choline (Cho). We therefore used metabolic modeling in conjunction with [(14)C]Cho labeling experiments and in vivo (31)P NMR analyses to define the constraints on GlyBet synthesis, and hence the processes likely to require further engineering. The [(14)C]Cho doses used were large enough to markedly perturb Cho and phosphocholine pool sizes, which enabled development and testing of models with rates dynamically responsive to pool sizes, permitting estimation of the kinetic properties of Cho metabolism enzymes and transport systems in vivo. This revealed that import of Cho into the chloroplast is a major constraint on GlyBet synthesis, the import rate being approximately 100-fold lower than the rates of Cho phosphorylation and transport into the vacuole, with which import competes. Simulation studies suggested that, were the chloroplast transport limitation corrected, additional engineering interventions would still be needed to achieve levels of GlyBet as high as those in plants that accumulate GlyBet naturally. This study reveals the rigidity of the Cho metabolism network and illustrates how computer modeling can help guide rational metabolic engineering design.